2015
DOI: 10.2174/1874091x01509010037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Cytochrome p450 (2C9) Enzyme in Iranian Baluch Ethnic Group

Abstract: The aim of the present study is to assess and compare the frequencies of the cytochrome P450 CYP2C9 variations in the Baluch ethnic group (n=110) with other ethnic groups. The allele frequencies of CYP2C9*1, CYP2C9*2 and CYP2C9*3 were 80.90%, 11.82% and 7.27%, respectively. 70.90%, 11.82%, 8.18%, 4.55%, 2.73% and 1.82% of subjects were with CYP2C9*1/*1, CYP2C9*1/*2, CYP2C9*1/*3, CYP2C9*2/*2, CYP2C9*2/*3 and CYP2C9*3/*3 genotypes, respectively. Different mutants may effect on prediction of drug dose requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…1 . Of the 30 articles screened for eligibility, ten were excluded for subjects not originating from the MENA region [ 17 26 ], seven were excluded for phenytoin concentrations not being assessed [ 27 33 ], five were excluded for both subjects not originating from the MENA region and phenytoin concentrations not being assessed [ 34 38 ], one was excluded for genetic polymorphisms not being assessed [ 39 ], and two were excluded for being poster abstracts [ 40 , 41 ]. Between the five included studies , CYP2C9*1, *2, and *3; CYP2C19*1, *2, and *3; and multidrug resistance protein 1 [ MDR1 , also known as ATP-binding cassette sub-family B member 1 (ABCB1)] C3435T polymorphisms were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . Of the 30 articles screened for eligibility, ten were excluded for subjects not originating from the MENA region [ 17 26 ], seven were excluded for phenytoin concentrations not being assessed [ 27 33 ], five were excluded for both subjects not originating from the MENA region and phenytoin concentrations not being assessed [ 34 38 ], one was excluded for genetic polymorphisms not being assessed [ 39 ], and two were excluded for being poster abstracts [ 40 , 41 ]. Between the five included studies , CYP2C9*1, *2, and *3; CYP2C19*1, *2, and *3; and multidrug resistance protein 1 [ MDR1 , also known as ATP-binding cassette sub-family B member 1 (ABCB1)] C3435T polymorphisms were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 82 studies were conducted within the MENA region and investigated the prevalence of CYP2C9 , CYP2C19 , and/or MDR1 variant alleles [ 27 , 29 , 42 121 ]. These studies were included in the secondary part of the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 24 ] With regard to ethnic diversity in Iran, epidemiological studies have been conducted to determine the distribution of CYP2C19 allele variants in different ethnic groups. [ 25 26 27 ] A recent study by Payan et al . revealed that 21.7% of Iranian population were carriers of CYP2C19*17 and 34.4% of studied population exhibited CYP2C19*1*17 and CYP2C19*17*17 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, these alleles may change the catalytic activity of CYP2C9 [6] and on the other hand, many studies have shown the variations among different ethnic groups. We have previously studied the genetic polymorphism of CYP2C9 gene among different ethnic groups in Golestan province [14,15]. This study aimed to assess the distribution of CYP2C9 allele and its genotypic variants in Sistani ethnic group in the city of Gorgan, South East of Caspian Sea, and North East of Iran.…”
Section: Introductionmentioning
confidence: 99%